Pattern Of Partnership Between Sugarcane Farmers And PT. Jhonlin Batu Mandiri In Bombana District - Eka Ayu Handayani; Bahari, Bahari; Sitti Aida Adha Taridala (International Journal of Technology and Education Research, 2024)
This study aims to understand the partnership model between sugarcane farmers and PT Jhonlin Batu Mandiri in Bombana Regency and to analyze the factors that influence sugarcane farmers' decisions to participate in the partnership with PT Jhonlin Batu Mandiri. The research was conducted from June 2021 to June 2024, involving a sample of 48 farmers, comprising 19 partner farmers and 29 non-partner farmers, determined using Slovin's formula. The data were analyzed using descriptive quantitative methods. The partnership model between sugarcane farmers and PT Jhonlin Batu Mandiri was examined using descriptive qualitative analysis with the approach of Miles and Huberman (2014). To analyze the factors influencing the decision of sugarcane farmers to join the partnership with PT. Jhonlin Batu Mandiri, binary logistic regression analysis was employed. The results of the study indicate that: Partnership patterns between sugarcane farmers and PT Jhonlin Batu Mandiri follows the nucleus-plasma pattern. In this pattern, the land used is owned by the plasma farmers. The nucleus company, PT Jhonlin Batu Mandiri, provides production facilities, technical management guidance, assistance with land preparation, provision of seedlings, fertilizers, harvesting labor, and takes on the processing and marketing of the production. The partner farmers are responsible for meeting the company's needs as agreed upon in the contract or agreement. The factors influencing the decisions of sugarcane farmers to join the partnership with PT Jhonlin Batu Mandiri are primarily the size of their land and capital limitations. Other factors, such as age, length of education, farming experience, and the use of agricultural technology, do not significantly impact their decision to enter into the partnership